Sensory Gardens: A multidisciplinary effort - Hussein, Hazreena (e-International Publishing House (e-IPH) Ltd., U.K., 2018)
This paper engages the users’ behaviour, their perceptions of use in sensory gardens and the reality faced by practitioners designing for these gardens, based on case-studies in the United Kingdom. Further investigation will be undertaken at Al-Bukhary International University in Malaysia once the completion of the country’s first sensory garden. Interview outcomes showed practitioners concurred on the design aspects that encourage the use of the area while the school staff had no strong views on the aesthetic value. Observation results showed pathway layout encourages behaviour, use and time spent in sensory areas. These outcomes are a significant argument in the conclusion. 2398-4295 © 2016. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK.. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. Keywords: Behaviour; British; Malaysia; sensory garden